T H E R O L E O F E X E C U T I V E C O A C H I N G I N L E A D E R S H I P D E V E L O P M E N T - Rumboll, Elaine Ann (My University, 2011)
In the United States alone, current annual spending on Executive Coaching is estimated at US$1billion. In South African organisations, the utilisation of executive coaches has increased substantially in the last four years. The reasons for this relate, among others, to the gradual changes in the structure of organisations; global exposure to international trends; shareholder pressure for executive performance; the demands for Black empowerment; the cost of the executive search; accelerated skills transfer; and the increasing focus on investment in people. Executive Coaching is viewed as a means to develop leadership ability with regard to both the individual skills of the executive as well as a means to increase awareness and more self-reflexive behaviour. Academic literature on Executive Coaching is scarce. Empirical studies into the effectiveness of executive coaching as a Leadership Development tool is rare. This empirical research was undertaken to ascertain the extent to which Executive Coaching might be able to contribute effectively to Leadership Development. The primary research methodology was by means of qualitative in-depth interviews with twenty stakeholders. A grounded-theory approach, relying on a hybrid of open and formal coding, was used in the analysis of the findings. Empirical research results indicate three kinds of attitudinal changes which occur as a result of executive coaching: greater insight into working at a senior level; a more effective understanding of roles in the organisation; and the development of a greater awareness of self and others. Nine skills are identified as being developed by Executive Coaching: improving networking ability; targeting developmental areas; trigging new behaviour; accelerated leadership development; time management; coping with conflict and iv change; more effective work relationships; improving focus; and honing strategic thinking. Findings demonstrate that Executive Coaching can contribute as an effective training and developmental tool for Leadership Development. Negative findings relate to: confusion on the part of the coachee around the purpose of Executive Coaching; the cost of Executive Coaching, sometimes without desirable results; the lack of strategic understanding of the organisation on the part of coach; and the negative consequences of coaches acting like consultants and imparting the wrong advice.
MBA thesis - WBS
Keywords: Leadership development; Coaching and mentoring; Executive coaching